Indirect Detection of Nitrogen-14 in Solid-State NMR Spectroscopy - Cavadini, Simone; Antonijevic, Sasa; Lupulescu, Adonis; Bodenhausen, Geoffrey (Chemphyschem, 2007)
NMR spectra of 14N (spin I=1) are obtained by indirect detection in powders spinning at the magic angle. The method relies on the transfer of coherence from a neighboring “spy” nucleus with S=1/2, such as 13C or 1H, to single‐ or double‐quantum transitions of 14N nuclei. The transfer of coherence can occur through a combination of scalar and residual dipolar splittings (RDS); the latter are also known as second‐order quadrupole–dipole cross terms. The two‐dimensional NMR spectra reveal powder patterns determined by second‐ and third‐order quadrupolar couplings. These spectra depend on the quadrupolar coupling constant CQ (typically a few megahertz), on the asymmetry parameter ηQ of the 14N nucleus, and on the orientation of the internuclear vector rIS between the I (14N) and S (spy) nuclei with respect to the quadrupolar tensor. These parameters, which can be subject to motional averaging, can reveal valuable information about the structure and dynamics of nitrogen‐containing solids. Application of this technique to various amino acids, either enriched in 13C or with natural carbon isotope abundance, with spectra recorded at various magnetic fields, illustrates the scope of the method. Magic angle: The transfer of coherence from neighboring nuclei, such as 13C or 1H, to single‐ or double‐quantum transitions of 14N nuclei enable 14N NMR spectra to be obtained. The experimental 14N double‐quantum powder pattern (— in picture) of L‐alanine is compared to the simulation (‐ ‐ ‐ ‐) to determine the quadrupolar coupling constant (CQ) and the asymmetry parameter (ηQ) of 14N.